Population Pharmacokinetics of Vancomycin in Kidney Transplant Recipients: Model Building and Parameter Optimization - Ma, Kui-fen; Liu, Yi-xi; Jiao, Zheng; Lv, Jun-hao; Yang, Ping; Wu, Jian-yong; Yang, Si (Frontiers in Pharmacology, 2020)
Abstract Background Depending on the renal function of patients and many other influencing factors, studies on vancomycin pharmacokinetics show significant inter- and intra-individual variability. The present study was conducted using a population pharmacokinetics method to investigate the pharmacokinetic parameters and identified their influencing covariates for intravenous vancomycin in adult kidney transplant recipients. Methods The drug monitoring data included 56 adult renal transplant recipients who received intravenous vancomycin as prophylactic medication. The analysis was performed by a population approach with NONMEM. Data were collected mainly during the first week after transplantation. Monitoring of vancomycin trough concentration in blood was initiated mainly 3-5 days after the initial administration. Results The one-compartment open model was optimal and adequately described the data. Body weight (WT) and estimated glomerular filtration rate (GFR) were identified as significant covariates of the pharmacokinetic parameters CL and V of intravenous vancomycin in the kidney transplant patients. The typical values of vancomycin CL and V were 2.08 L h-1 and 63.2 L, respectively. A dosage strategy scheme according to model results was also designed. Conclusion Both WT and GFR of the kidney transplant patients positively influence the pharmacokinetic parameters CL and V for intravenous vancomycin. Our population pharmacokinetic model provides a reference for vancomycin dosage adjustment in kidney transplant recipients.